2013
DOI: 10.1021/pr300869h
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Early HIV-1 Nucleoprotein Complexes

Abstract: After entry into the cell, the early steps of the human immunodeficiency virus type 1 (HIV-1) replication cycle are mediated by two functionally distinct nucleoprotein complexes, the reverse transcription complex (RTC) and preintegration complex (PIC). These two unique viral complexes are responsible for the conversion of the single-stranded RNA genome into double stranded DNA, transport of the DNA into the nucleus, and integration of the viral DNA into the host cell chromosome. Prior biochemical analyses sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 128 publications
0
35
0
Order By: Relevance
“…CypB has been identified in a number of proteomic studies of HIV infected cells and purified virions (Chertova et al, 2006; Haverland et al, 2014; Schweitzer et al, 2013), including a recent study in which we observed that it was increased in the nuclei of HIV infected Jurkat T-cells (DeBoer et al, 2014). To extend those observations we investigated the subcellular expression of CypB in primary peripheral blood mononuclear cells (PBMCs) during HIV infection (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…CypB has been identified in a number of proteomic studies of HIV infected cells and purified virions (Chertova et al, 2006; Haverland et al, 2014; Schweitzer et al, 2013), including a recent study in which we observed that it was increased in the nuclei of HIV infected Jurkat T-cells (DeBoer et al, 2014). To extend those observations we investigated the subcellular expression of CypB in primary peripheral blood mononuclear cells (PBMCs) during HIV infection (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Cyclophilin B (CypB) was identified in a number of proteomic investigations performed by our laboratory, including: a characterization of the interactome of Matrix and Integrase, a study of partially purified preintegration complexes, and a study of the nuclei of HIV-infected T-cells ((DeBoer et al, 2014; Schweitzer et al, 2013; Schweitzer et al, 2012), unpubublished data ). Additionally, CypB was shown to be significantly upregulated in the nuclei of HIV-infected monocyte-derived macrophages (Haverland et al, 2014) and identified as an HIV-dependency factor (Brass et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We initially identified NonO interacting with PICs in HIV-1-infected CD4 + T cell lines, 9 and subsequent studies have also identified NonO to be an HIV-1 interactant. [10][11][12] However, the significance of these interactions and whether NonO plays a crucial role in HIV-1 infection have not been answered. We addressed these questions by investigating the effect of NonO KD on HIV-1 infection and characterized what stages of the replication cycle were affected.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of fractions from HIV-1-infected T cell lines identified NonO as a component of HIV-1 RTC across seven repeat experiments. 10 NonO was also shown to interact with several HIV-1 proteins (including integrase) ectopically expressed in HEK293 and Jurkat cells. 11 Furthermore, NonO was identified in an analysis of the Rev interactome in HeLa cells, and the association between NonO and Rev was enhanced by the presence of the Rev response element.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 25 proteins identified from four replicate experiments, both the eEF1A and eEF1G subunits of eEF1 were identified as functional RT cofactors, providing a basis for studying RT and trafficking of the RTC to the nucleus. In a similar study, proteomic analysis was carried out in RTCs and PICs partially purified by gradient centrifugation fractionation [53]. LC-MS/MS analysis of seven replicates identified 94 cellular proteins unique to the infected fractions.…”
Section: Extended Ap-ms-based Methodologiesmentioning
confidence: 99%